International Collaboration for Grassroots Social Innovation: An Analysis of Agents, Goals, Drivers, and Processes of the SUIJI Program - Koichi, Ohashi; Tamma, Sukri; Ibrahim, Muhammad Akmal; Hasniati, ‎; Rampisela, Dorothea Agnes; Nelsi, Oktaviani (KnE Social Sciences, 2025)
International collaboration is increasingly recognized as a significant driver in addressing social and environmental challenges, particularly through grassroots social innovation. This study uses the capability approach to explore the role of the Six Universities Initiative Japan-Indonesia (SUIJI) in supporting community-based social innovation in Indonesia. The aim is to analyze how cross-cultural collaboration between Japanese and Indonesian students influences the capabilities of local communities. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis. The research participants included students, faculty members, and local community leaders in the SUIJI program. The findings indicate that the SUIJI program successfully enhanced local community capabilities, particularly regarding technical skills and participation in decision-making processes. However, Japanese students faced cultural adaptation challenges due to differences in work approaches and the absence of communitybased programs in their curriculum. To address this, it is recommended that universities in Japan integrate programs like Kuliah Kerja Nyata (KKN) into their curricula. These findings have important implications for higher education policy and highlight the need for curriculum adaptation to improve the effectiveness of international collaboration in grassroots social innovation. This study underscores the critical role of community ownership, local capacity building, and institutional support in sustaining grassroots innovation. Furthermore, it provides valuable insights into how the integration of the capability approach within social innovation practices can have a transformative impact on cross-national educational collaborations.